A reproductive health-care program for surrogate mothers: A mixed methods study - Marjan Goli; Shahnaz Kohan; Seiied Mahdi Ahmadi Oloonabadi; Ziba Farajzadegan; Zeinab Heidari (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Surrogacy has become an alternative family formation option for women who are unable to carry a pregnancy. There is no comprehensive care program despite the different nature of this pregnancy. The present study aimed to develop a reproductive health-care program for surrogate mothers within the cultural and social context of Iran. MATERIALS AND METHODS: In the present sequential exploratory mixed methods study, first through a qualitative approach surrogate mothers, care providers, and policy makers of reproductive health services were selected purposefully. Data were collected by using the in-depth semi-structured interviews and analyzed. A care program draft was designed by integrating results of the qualitative study and reviewing the literature and guidelines, then appropriateness of each proposed care was assessed by a two-Rounds Delphi technique (RAM), and the final reproductive health-care program for surrogate mothers was developed. RESULTS: The surrogate mothers' reproductive health needs were summarized in four main categories: surrogate mothers' extra care, educational training, psychological support, and protecting against surrogacy's social and familial consequences. The reproductive health-care program for surrogate mothers were developed in four sections: prepregnancy health screenings and legal counseling; special care during embryo transfer until pregnancy confirmation; psychological support and prenatal care of surrogacy until delivery and follow-up postpartum care. CONCLUSION: Women face many challenges in surrogacy and need special care such as legal counseling, reproductive health care, and psychological support. Implementation of this care program seems to help improve the reproductive health of these mothers.